EFEKTIVITAS PEMBELAJARAN DARING SELAMA MASA PANDEMIC PADA MATA PELAJARAN MATEMATIKA - Yasika Egi Putri Chika (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
Abstract This study aims to determine the effectiveness of online learning during the pandemic. This research is a qualitative research with descriptive method. The subjects of this study were 5 grade IX students of SMP Negeri 24 Tangerang. The data collection technique used a questionnaire questionnaire containing questions about student responses to online learning in mathematics. Data analysis in this study used descriptive statistical analysis. The results of the study are shown from the results of the calculation of the percentage of student responses to online learning in mathematics subjects is 60% with the qualification criteria